2013
DOI: 10.1364/boe.4.001978
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric imaging and quantification of cytoarchitecture and myeloarchitecture with intrinsic scattering contrast

Abstract: Abstract:We present volumetric imaging and computational techniques to quantify neuronal and myelin architecture with intrinsic scattering contrast. Using spectral / Fourier domain Optical Coherence Microscopy (OCM) and software focus-tracking we validate imaging of neuronal cytoarchitecture and demonstrate quantification in the rodent cortex in vivo. Additionally, by ex vivo imaging in conjunction with optical clearing techniques, we demonstrate that intrinsic scattering contrast is preserved in the brain, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
55
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 34 publications
11
55
1
Order By: Relevance
“…7 The various research studies done so far with this method have used different types of biological tissues and optical clearing agents (OCAs) to obtain the decreased light scattering during the applied treatments. [7][8][9][10][11][12][13][14][15][16][17][18] The transparency effect initiates with the administration of an OCA to the tissue, which can be made topically or by tissue immersion in the agent. Once the OCA enters in contact with the tissue, the optical transparency effect is created through the cooperation of two mech- 18 cal tissues present a characteristic high-scattering coefficient and anisms: tissue dehydration and RI matching.…”
Section: Introductionmentioning
confidence: 99%
“…7 The various research studies done so far with this method have used different types of biological tissues and optical clearing agents (OCAs) to obtain the decreased light scattering during the applied treatments. [7][8][9][10][11][12][13][14][15][16][17][18] The transparency effect initiates with the administration of an OCA to the tissue, which can be made topically or by tissue immersion in the agent. Once the OCA enters in contact with the tissue, the optical transparency effect is created through the cooperation of two mech- 18 cal tissues present a characteristic high-scattering coefficient and anisms: tissue dehydration and RI matching.…”
Section: Introductionmentioning
confidence: 99%
“…Our result shows that the morphology of brain tissue between OCM and the stained histological section has a strong correlation. In particular, OCM images have even better contrast for the fiber bundles in the region of the corpus callosum (cc), caudoputamen (CP), and cerebral peduncle (cpd) because light scattering in the lipids of myelin fiber are relatively stronger than the surrounding tissue [10]. One of the strong advantages of widefield OCM imaging is the simple preparation of brain tissue and noninvasive imaging capability.…”
Section: Lettermentioning
confidence: 99%
“…For the last decade, optical clearing technique to improve the imaging depth has been actively investigated [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. As the mismatch in refractive index (RI) between cellular components in tissue is the major cause of light scattering, selective removal of cellular components with relatively low or high refractive index can reduce the light scattering and make the tissue more optically transparent.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used approach is replacing interstitial fluids (RI~1.33) in inter-and intra-cellular space with optical clearing agents (OCAs) which have refractive indices of ~1.46, matched to the average refractive index of most biological samples. It has been demonstrated that several OCAs such as glycerol [26- [30][31][32] and BABB [33] can enhance imaging depth in various organs such as brain [22][23][24][25][26], skin [27][28][29], pancreas [30], colon [31] and heart [32][33][34]. However, optical clearing effect of OCAs on LN has not yet been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%